The double edge to parasite escape: invasive host is less infected but more infectable. Issue 9 (22nd August 2017) - Keogh, Carolyn L.; Miura, Osamu; Nishimura, Tomohiro; Byers, James E.
Abstract: Nonnative species that escape their native‐range parasites may benefit not only from reduced infection pathology, but also from relaxed selection on costly immune defenses, promoting reallocation of resources toward growth or reproduction. However, benefits accruing from a reduction in defense could come at the cost of increased infection susceptibility. We conducted common garden studies of the shore crab Hemigrapsus sanguineus from highly parasitized native (Japan) populations and largely parasite‐free invasive (USA) populations to test for differences in susceptibility to infection by native‐range rhizocephalan parasites, and to explore differences in host resource allocation. Nonnative individuals showed at least 1.8 times greater susceptibility to infection than their native counterparts, and had reduced standing metabolic rates, suggesting that less of their energy was spent on physiological self‐maintenance. Our results support an indirect advantage to parasite escape via the relaxation of costly physiological defenses. However, this advantage comes at the cost of heightened susceptibility, a trade‐off of parasite escape that is seldom considered.